THE PATTERN OF THE ḤUFFĀŻ’S TEACHING-LEARNING PROCESS - Moh. Khoeron (Widyariset, 2012)
This is a study of ‘Biografi Ḥuffāż di Indonesia’ which aimed to describe ḥuffāż’s teaching-learning process.The data were described and analyzed according to relevant theories, in order to give a clear description of theirprocess. The final result showed the variety of ḥuffāż’s teaching-learning process. Ḥuffāẓ learning patterns canbe grouped into three, namely: a) from the kitab kuning learning and memorizing the Quran; b) of memorizing theQuran and study kitab kuning; c) of the kitab kuning to learn, memorize the Quran, then return to the kitab kuning.Patterns of teaching based on talaqqī and musyāfahah. The method includes talaqqī, musyāfahah, sima’an,ngeloh, murā ja’ah, mudārasah, and takrār.